WACIKA PARISUDA : ETIKA UJARAN DALAM HINDU - - Wentin (Fakultas Dharma Duta, 2017)
This paper is an explanation of the ethical teaching of speech according to Hinduism. In Hinduism, the quality of one's self is measured at least on three aspects of action, known as Tri Kaya Parisuda (Three Good or noble Behavior), 1) Manacika (good thinking), 2) Wacika (good speech), and 3) Kayika (good action). All three things must be actualized in a balanced way. If there is lameness in one of the other aspects, it will have a bad effect. Man is recognized by the way he thinks, speaks and acts. This paper traces the teachings of wacika parisuda (good speech) from various sources in Hindu literature. In the study of Hindu literature (Nitisastra, Slokantara, Sarasamuccaya, Bhagavadgita) shows that a person's utterance indicates his maturity, knowledge, and spirituality.